(3JbjjO aj PcQ CTQGa GdYdejjfs - (3GdUGOb Hf QjShfs
(3ChdgG (B:s
(3PcQ GdCTQGa GdYdejjf (B: (3LOge GdLGeY dJTYHge HCSQge gh GdTjN CHh HcQ , Oajf Yjf GdMQjQ HZGHI GdbQc bHjdI Hfi YQhS GdeSeGI YfOgG dg eMHI ai Pdc GdLGfHI CTQGa Cgd GdHjJ HgG s
(3BNQgG (B:s
(3hCeG ChdGO SjOi YHO GdUeO Hf GdbWH GdLGeY ehdGfG YHO GdSdGe , faYfG Gddg Hg hHge hge Ydi aQbJjf , dG KGdK dgeG bjO ef JCdja GdYdGei GdcGJH SjOi GdUGOb Hf QjShf , dWa Gddg Hg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B_ (3GdQHGW (B(1512 (3O (B/ 2) s
Keywords: (3GdJGQjNs